Management of Dengue Fever and Morbidly Obese in Pregnancy after C-Section - Mohtar, Dear; Erlangga, Erias (Journal of Society Medicine, 2023)
Introduction: Dengue is endemic to the Southeastern geographical area of Asia (SEA), spreading through the mosquito vector Aedes aegypti. There is also evidence to suggest a higher percentage of severe dengue infections happening to pregnant women than non-pregnant women. Case Report: The patient was 28 years old, weight 120 kg, height 162 cm, admitted to the Emergency Department (ED) of Hasan Sadikin Hospital (RSHS) with dyspnea in pregnancy. Anamnesis obtained that the patient complained of fever since 5 days ago, the last 1 day felt increasing shortness of breath. Intraoperatively lasted 3 hours with bleeding 4300 ml. The patient was admitted to the ICU for 5 days of treatment and was extubated on the 4th day Conclusion: Dengue Fever with morbid obese in pregnancy is a threat of morbidity and mortality. The main pathophysiology that occurs is changes in hematological and respiratory physiology in pregnancy which will aggravate the patient's condition. The principle of therapeutic management in the ICU lies in optimization, stabilization and evacuation of fluids and handling mechanical ventilation